New method for algae comprehensive utilization: Algae-derived biochar enhances algae anaerobic fermentation for short-chain fatty acids production. (October 2019) - Duan, Xu; Chen, Yunzhi; Yan, Yuanyuan; Feng, Leiyu; Chen, Yinguang; Zhou, Qi
Graphical abstract: Highlights: Algae-derived biochar benefited SCFAs yield and generation rate. Disruption of algae cell structure and hydrolysis of algae were promoted. Communities and survival of acidogenic anaerobes were improved. Electron transport and ATP synthesis were strengthened by algal biochar. Abstract: Interest in the resource utilization of algae has gradually increased due to the frequent occurrence of harmful algal blooms. Here, biochar derived from algae was applied to algae anaerobic fermentation for short-chain fatty acids (SCFAs) production. In the presence of algae-derived biochar, the concentration of SCFAs within 4 d (4334 mg COD/L) was approximately doubled compared to the control (2016 mg COD/L), and the fermentation time for maximal SCFAs yield was shortened. Biochar improved the disruption of algae to release more intracellular macromolecular organics. Altering algae hydrolysis, the activity of hydrolase and the contents of functional gene were advantageous to SCFAs accumulation by providing more micromolecular organics in the presence of biochar. Additionally, the relative abundance and survival of acid-forming bacteria were enhanced significantly. Furthermore, biochar accelerated the electron transport and energy synthesis in the biological system, driving the biological reactions that allow microorganisms to function and life to flourish.